Influence of interacting heavy nuclei mass asymmetry on capture cross-section in fusion reactions - Anokhin, R.A.; Pavlii, K.V. (Вопросы атомной науки и техники, 2013)
The effect of beam and target isotope configuration on the capture cross-section is considered using dynamic-statistical description of the first stage of heavy nuclei fusion reactions. It demonstrates that the isotopic configuration of heavy nucleus renders insignificant effect on the capture cross-section. Cross-section decreases by decreasing mass asymmetry due to the change of light nuclei isotope configuration. The capture cross-section increases by increasing charge asymmetry for constant number of nucleons in the compound nucleus. For odd-odd interacting nuclei capture cross-section is from 1.5 to 6 times greater than for even-even nuclei in the same value of protons and neutrons in the compound nucleus. Використовуючи динамiко-статистичний опис першої стадiї реакцiї злиття важких ядер, розглядається вплив iзотопної конфiгурацiї пучка та мiшенi на перерiз захоплення. Показано, що iзотопна конфiгурацiя важкого ядра незначно впливає на перерiз захоплення. При зменшеннi масової асиметрiї зарахунок змiни iзотопної конфiгурацiї легкого ядра перерiз зменшуєтьсяi призбiльшеннi зарядової асиметрiї, для постiйної кiлькостi нуклонiв в складеному ядрi, перерiз захоплення збiльшується. Для непарно-непарних взаємодiючих ядер перерiз захоплення в 1,5...6 разiв бiльше, нiж для парно-парних ядер при одному i тому ж значеннi протонiв та нейтронiв в складеному ядрi. Используя динамико-статистическое описание первой стадии реакции слияния тяжелых ядер, рассматривается влияние изотопной конфигурации пучка и мишени на сечение захвата. Показано, что изотопная конфигурация тяжелого ядра незначительно влияет на сечение захвата. При уменьшении массовой асимметрии за счет изменения изотопной конфигурации легкого ядра сечение уменьшается и при увеличении зарядовой асимметрии, для постоянного количества нуклонов в составном ядре, сечение захвата увеличивается. Для нечетно-нечетных взаимодействующих ядер сечение захвата в 1,5...6 раз больше, чем для четно-четных ядер при одном и том же значении протонов и нейтронов в составном ядре.